2011
DOI: 10.1124/jpet.111.187583
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Methadone Treatment Shows a Better Cost/Benefit Ratio than Chronic Morphine in Mice

Abstract: Chronic treatment of pain with opiate drugs can lead to analgesic tolerance and drug dependence. Although all opiate drugs can promote tolerance and dependence in practice, the severity of those unwanted side effects differs depending on the drug used. Although each opiate drug has its own unique set of pharmacological profiles, methadone is the only clinically used opioid drug that produces substantial receptor endocytosis at analgesic doses. Here, we examined whether moderate doses of methadone carry any ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 43 publications
0
15
1
Order By: Relevance
“…This difference may explain the reduced tolerance of methadone relative to morphine (morphine characteristically induces little MOR internalization; refs. 25,26). But this difference would predict weaker dopaminergic activation by morphine, which is the opposite of what we observed in the present study.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…This difference may explain the reduced tolerance of methadone relative to morphine (morphine characteristically induces little MOR internalization; refs. 25,26). But this difference would predict weaker dopaminergic activation by morphine, which is the opposite of what we observed in the present study.…”
Section: Resultscontrasting
confidence: 99%
“…Methadone is also pharmacodynamically different from morphine in that it has a greater ability to promote MOR internalization and the consequent recycling of nondesensitized MOR (25,26). This difference may explain the reduced tolerance of methadone relative to morphine (morphine characteristically induces little MOR internalization; refs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, opioid combinations of morphine with low-dose DAMGO (He et al, 2002) or methadone (He and Whistler, 2005), which are MOR agonists with substantial MOR internalization ability, diminished both morphine tolerance and dependence in rats. However, when using a mixture of agonists, it is difficult to strongly conclude that MOR endocytosis contributes to morphine tolerance/dependence because numerous sets of MOR signaling pathways are modified by each agonist (Alvarez et al, 2002;Blanchet et al, 2003;Enquist et al, 2012;He et al, 2009;Milan-Lobo and Whistler, 2011) according to the so-called agonistselective theory (Zheng et al, 2010). A previous study indicated that morphine induces MOR endocytosis in mutant L83I (mouse orthologue of human L85I) without altering binding affinity or cAMP signaling.…”
Section: Introductionmentioning
confidence: 99%